Exploring the Omani Rub’ Al-Khali (2023-2024): Archaeological and Geomorphological Investigations in Maitan and Wadi Stum - Charpentier, Vincent (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2023)
Keywords: Archéologie -- Oman

Special Surface Finds from Old Wibil, an Iron Age Site in Ar Rustaq, Sultanate of Oman - Douglas, Khaled; Gernez, Guillaume; Hesein, Mohamad A. (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

Iron Age landscape in the Tanuf District, Ad-Dākhliyyah Governorate: A transmountain hypothesis based on surveys and excavations in 2017–2023 - Kuronuma, Taichi; Miki, Takehiro; Tanabe, Kantaro; Kondo, Yasuhisa (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

A Set Of Early Iron Age Discovered at Dhat Khayl Near Al-Hamra (Ad-Dakhiliyah), Oman - Gernez, Guillaume (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

A Wadi Suq Necropolis in The Mountains Rescue Excavations at Bilad Ash Shuhum (Adh-Dhahira, Oman) - Gernez, Guillaume; al-Ghafri, Waleed; Ciesielski, Elsa (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

The Collective Corridor-Shaped Tombs of The Daba Al Bayaah Necropolis (Musandam, Oman): The Origin and Spread of A Funerary Structure Based On Evidence From South-East Arabia - Genchi, Francesco (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

Rupelian Fossil Elasmobranch from Omani Thaytiniti Fauna Fill A Chronological Gap in The Elasmobranch Fossil Record of West Indian Ocean - Adnet, Sylvain; Cappetta, Henri; Charpentier, Vincent (Journal of Oman Studies, 2023)
Keywords: Archéologie -- Oman

Ship timbers from the Islamic sites of al-Balid and Qalhat, Oman: sewn-plank technoloy in the Indian Ocean during the 10-16th centuries CE - Ghidoni, Alessandro (Nautical archaeology society monograph series, 2023)
The sewn-plank ships that sailed the Indian Ocean during the medieval Islamic period carried people, goods, and ideas between East Africa, Arabia, India, and China. Despite their key role, we know relatively little about them. To date, archaeological work related to sewn boats in the region has been limited, while the few textual references generally lack crucial details regarding their design, structure, and operation. Due to the paucity of archaeological evidence until 20 years ago, the study of medieval shipbuilding in the region has often been flawed by Orientalism and fuelled by principles of the Enlightenment in early studies. Scholars had previously approached this topic through a European lens, typically with a strong colonialist attitude, and viewed this technology as basic, primitive, and incapable of developing without an external force, such as the more technologically advanced Europe. This book presents the first comprehensive study on medieval sewn boats of the Indian Ocean, using new and original data. It provides a technical analysis of the ship timbers recently discovered at al-Balid and Qalhat, Oman, in a comparative context. Pieces are examined from a material perspective, and then compared with textual, iconographic, ethnographic, archaeological, and experimental archaeological evidence. It contextualizes the ship timbers within the broader material networks in the Indian Ocean during the medieval Islamic period, thereby increasing our knowledge of maritime communities and their shipbuilding technology.
Keywords: Archéologie -- Oman; Navigation -- Oman

Qalhat, A Medieval Port City of Oman. From a field of ruins to UNESCO - Rougeulle, Axelle (The Archaeological Heritage of Oman, 2023)
Although it is one of the main archaeological sites in Oman, the medieval port of Qalhat, near Sur in Ash-Sharqiyah Governorate, has long remained poorly documented. The extensive research initiated in 2008 by the Ministry of Heritage and Tourism (at the time, Heritage and Culture) shed striking light on the history of this famous harbour city, which was the twin capital of the Kingdom of Hormuz from the 13th to the 16th century. Surface surveys and excavations have revealed the plan and chronology of the city and its different districts. Mosques (including the Great Mosque built by Bibi Maryam around 1300) and other religious buildings, fortifications, and water supply systems have been identified and studied. The craft and economic activities of the city and the regional and international commercial links of the port have been reconstructed, as well as the daily life of its inhabitants, revealing the wealth and cosmopolitan character of this ancient Omani metropolis. All these results highlighted the Outstanding Universal Value of the site and eventually led to the inscription of Qalhat on the UNESCO World Heritage List in 2018.
Keywords: Archéologie -- Oman

Persistent pastoralism: monuments and settlements in the archaeology of Dhofar - McCorriston, Joy (The Archaeological Heritage of Oman, 2023)
A summary of archaeological teamwork along the Dhofar plateau and its backslope into the Nejd of Southern Oman, this book documents survey and excavation of small-scale stone monuments and pastoral settlements. Whether used as burial places, as landmarks, as mnemonic devices, or for other purposes, monuments are the enduring and prominent traces of desert pastoralists. In Dhofar, pastoralists constructed monuments in discrete pulses over 7500 years. Recognizing the dynamic ecosystems and climate regimes of Arabian prehistory, the author suggests that mobile pastoralists used monuments to link dispersed households into broader social communities. Furthermore, the range of practical adjustments to monuments as a consistent means of messaging among mobile people showcases the adaptive strength of Dhofar?s prehistoric inhabitants over time. A singular episode of settlement during a particularly arid period highlights the longer tradition of pastoral people on the move. With fictional vignettes to imagine the people who used these monuments, the chapters introduce archaeological analysis of the social identities, patterns of resource access, contacts, aversions, and exchanges with neighboring groups. Finally, the book underscores the rich heritage of persistent pastoralism within contemporary Oman
Keywords: Archéologie -- Oman

Rock Scenes of Goats and Herders in Dhofar: An Analogy with the Dhofari Traditional Goatherds - El-Mahi, Ali Tigani (أدوماتو, 2023)
Keywords: Archéologie -- Oman

After the Fall of the Caravan Kingdoms. Notes about the Occupation of Sumhuram and the Area of Khor Rori (Oman) from the Fifth Century AD to the Islamic Period - Pavan, Alexia (Études et Travaux, 2023)
Since the beginning of the investigations in the area of Khor Rori and at the site of Sumhuram, the easternmost outpost of the caravan kingdoms along the southern coast of the Arabian Peninsula, cultural material and architectural evidence seemed to exclude frequentation, both permanent and seasonal, during the Islamic period. Indeed, it was assumed that any form of occupation, which had begun in the second century BC, ceased in the fifth century AD, consistent with the historical, economic and cultural scenario that marked the end of the caravan kingdoms. However, discoveries made during more recent fieldwork, along with a critical reinterpretation of previously collected data, have clearly demonstrated the existence of a late occupation of the area, which can be tentatively dated to the Late Antique period in the case of the burials located nearby and to the Islamic period in the case of the reoccupation of the site. This paper will discuss the preliminary results of the re-analysis of the late evidence, focusing on the last architectural structures, the small finds and some of the pottery.
Keywords: Archéologie -- Oman

Fulayj: a Sasanian and early Islamic fort in the Sohar hinterland - Priestman, Seth (Proceedings of the Seminar for Arabian Studies, 2023)
Until 2018 knowledge of al‑ʿUlā County’s archaeology had been limited to a few key sites. Since then, an extensive archaeological landscape survey has been conducted on behalf of the Royal Commission for AlUla (RCU) across a large area (3302 km2) centred in and around the al‑ʿUlā valley (excluding the oasis and the key heritage sites of Dadan, Ḥegrā (al‑Ḥijr), Qurḥ (al‑Mābiyāt), and Old Town), as a part of the broader Identification and Documentation of Immovable Heritage Assets (IDIHA) survey. The IDIHA project aims to identify heritage assets in advance of the anticipated increase in visitors and facilitate further research. Data collected through remote sensing and ground recording of sites has been integrated into a customized heritage geodatabase. Over 16,000 sites have been recorded in the main al‑ʿUlā valley over three years by the ground survey, demonstrating an intensive occupation of the area from the Palaeolithic through to the present, including a rich range of domestic, agro-pastoral (including water management), funerary, defensive, ritual/religious, infrastructure/transport, productive and hunting sites, as well as communication/artistic (rock art and inscriptions — the largest category in terms of overall numbers of sites). In parallel with the survey, targeted excavations explored a selection of mostly late prehistoric sites and feature types in order to develop an understanding of the chrono-cultural development of the landscape, adding considerable data to our knowledge of the archaeology of north-western Arabia.
Keywords: Archéologie -- Oman

Une tombe vieille de sept mille ans à Oman abrite des dizaines de squelettes préhistoriques - Groterria, Antoine (2023)
À Oman, au sud de la péninsule arabique, des scientifiques ont exhumé les squelettes de dizaines de personnes enterrées il y a sept mille ans. C'est l'un des plus anciens édifices humains connus dans ce pays.
Keywords: Archéologie -- Oman